Pengaruh Pengaruh Model Course Review Horay (CRH) Berbantuan Media Tebak Gambar Terhadap Keaktifan Belajar Siswa SD - Muhamat Hasim Pamungkas; Yasir Arafat; Susanti Faipri Selegi (Jurnal keilmuan dan Kependidikan dasar, 2025)
The success of the learning process is influenced by many factors, wich include student activeness. Learning activeness can be enhanced through the use of appropriate instructional models. Course Review Horay (CRH) combined with “Guess the Picture” media is an innovative approach that creates an engaging and interactive learning experience. This study aims to examine the effect of the CRH learning model assisted by “Guess the Picture” media on the learning activeness of fifth-grade elementary school students in the IPAS (Integrated Natural and Social Sciences) subject. This research is a quantitative study using an experimental method with a One Group Pretest-Posttest design. The population consisted of all fifth-grade students at SDN Eling-Eling. The sampling technique used was a census/total sampling, where all members of the population were used as the sample. Data collection techniques included questionnaires and documentation. The data analysis technique used was the Paired Sample t-test. The analysis results showed that the average pre-questionnaire score in the experimental class was 18.26, while the average post-questionnaire score was 23.07. The hypothesis test using the Paired Sample t-test showed a significance value of sig (2-tailed) = 0.000 < 0.05. This indicates that the CRH learning model assisted by “Guess the Picture” media has a significant effect on the learning activeness of fifth-grade students in the IPAS subject. Therefore, the CRH learning model with “Guess the Picture” media can be a viable solution to improve student learning activeness, particularly in the IPAS subject.